Tissue clearing applications in memory engram research - Yip, Kwok Yui Tony; Gräff, Johannes (Frontiers in Behavioral Neuroscience, 2023)
A memory engram is thought to be the physical substrate of the memory trace within the brain, which is generally depicted as a neuronal ensemble activated by learning to fire together during encoding and retrieval. It has been postulated that engram cell ensembles are functionally interconnected across multiple brain regions to store a single memory as an ‘engram complex’, but visualizing this engram complex across the entire brain has for long been hindered by technical limitations. However, with the recent development of tissue clearing techniques, advanced light sheet microscopy and automated 3D image analysis, it has now become possible to generate a brain-wide map of engram cells. Doing so, novel brain regions and circuits can be identified for subsequent functional manipulations, thus providing an opportunity to robustly examine the postulation of an “engram complex” underlying memory storage. In this review, we first provide a comprehensive summary of whole-brain engram mapping studies. We then compile a guide on implementing the optimal tissue clearing technique for engram tagging approaches, paying particular attention to visualize engram reactivation as a critical mnemonic property, for which whole-brain multiplexed immunostaining becomes a challenging prerequisite. At last, we highlight the potential of tissue clearing to simultaneously shed light on both the circuit connectivity and molecular underpinnings of engram cells in a single snapshot.